Design of metal plate temperature sensor based on fiber bragg grating (FBG) - Nani Fadzlina Naim; Nur Shahira Anuar; Suzi Seroja Sarnin; Norsuzila Yaa’cob (Institute of Advanced Engineering and Science, 2019)
This paper presents the design and characterization for metal plate temperature sensor based on Fiber Bragg Grating (FBG). Five types of FBGs were used such as Acrylate FBG, Bare FBG, Bimetallic Acrylate FBG, Bimetallic Bare FBG and Ceramic FBG to determine the sensitivity on four different plates at 23℃ to 70℃, experimentally. The four different plates are Aluminium, Aluminium Coating, Zinc and Zinc Coating has been used because of their excellent thermal conductivity. Two metals which are Copper and Zinc have been chosen to design the Bimetallic Strips FBG due to the Coefficient Thermal Expansion (CTE) to improve their sensitivity. The results show that Ceramic FBG has been chosen as the best temperature sensor because it has the highest sensitivity compared to other FBGs with sensitivity value of 50.4 and 59.7 pm 16(â„ƒ)-1